FORMATION OF THE DISCLINATION DEFECTS IN THE DYE-DOPED CHOLESTERIC LIQUID CRYSTALLINE STRUCTURE UNDER THE INFLUENCE OF THE LASER BEAM - Ninoyan, Zh.V. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2018)
In the work the influence of the laser beam on the optical properties of highly absorbing dye-doped cholesteric liquid crystalline (CLC) structure is investigated. By means of polarizing microscope studies step-like variation of the CLC helical pitch and formation of the disclination defect lines (oily streaks) is observed.
Keywords: chirality; pitch; lasing; defects; dye; domain